2020
DOI: 10.3390/ijerph18010082
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Anxiety Symptoms: Rates and Risk Factors in Mexican Women

Abstract: Anxiety during pregnancy and after childbirth can have negative consequences for a woman and her baby. Despite growing interest in the perinatal mental health of Mexican women living in the U.S., perinatal anxiety symptom (PAS) rates and risk factors have yet to be established for women in Mexico. We sought to determine PAS rates and identify risk factors, including the traditional female role (TFR) in a sample of Mexican women. This secondary data analysis is based on 234 Mexican women who participated in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
5
8
0
Order By: Relevance
“…Almost one-third (33/120, 27.5%) of participants screened met the cutoff score for maternal depression, which is higher than what was previously reported in the literature for immigrant women and other immigrant groups in Australia [ 21 ], Canada [ 22 - 25 ], and Norway [ 26 ]. Moreover, 12.1% (14/116) met the criteria for increased anxiety symptoms, which is similar to the findings in previous studies [ 27 - 29 ]. It is evident that African immigrant women are exposed to many factors following childbirth, which can impact their maternal mental health, such as lack of social support, weak sense of belonging in the local community, and economic factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Almost one-third (33/120, 27.5%) of participants screened met the cutoff score for maternal depression, which is higher than what was previously reported in the literature for immigrant women and other immigrant groups in Australia [ 21 ], Canada [ 22 - 25 ], and Norway [ 26 ]. Moreover, 12.1% (14/116) met the criteria for increased anxiety symptoms, which is similar to the findings in previous studies [ 27 - 29 ]. It is evident that African immigrant women are exposed to many factors following childbirth, which can impact their maternal mental health, such as lack of social support, weak sense of belonging in the local community, and economic factors.…”
Section: Discussionsupporting
confidence: 90%
“…For maternal anxiety, however, the rate of 12% in this study is comparable to the rates in other studies on Mexican immigrant women in the United States (18%) [ 29 ], Chinese immigrant women in Canada (18.4%) [ 28 ], and African immigrants in the United States (12.4%) [ 27 ]. Maternal anxiety as a whole is an understudied area among African immigrant women, and thus, there is a scarcity of comparable literature.…”
Section: Discussionsupporting
confidence: 82%
“… 26 On the one hand, perceptions of equity and time spent on housework are related to depression in women. 27 On the other hand, adherence to traditional female roles 28 and the identity of a housewife are associated with prenatal anxiety. 29 Results of our study showed that the assignment of family tasks may have failed to readjust in early pregnancy, and pregnant women, who usually suffer from physical discomfort, 14 tend to hold a worse view of family functioning in the domain of roles, which seems to play an important role in their mood symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized anxiety disorder (including anxiety not specified) was the most commonly reported anxiety disorder, examined by 184 of 203 studies (90.6%) . The pooled point prevalence for generalized anxiety disorder was 22.2% (95% CI, 19.4%-25.0%; n = 173 553).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 10 617 studies; 1231 full texts were reviewed, and of these, 203 studies were included (Figure 1; eTable 2 in Supplement 1). Cumulatively, outcomes were reported for 212 318 perinatal women (from conception to 12 months post birth) from 33 LMICs. The prevalence estimates of 6 anxiety and related disorders were reported: generalized anxiety disorder, social anxiety disorder, posttraumatic stress disorder, obsessive-compulsive disorder, panic disorder, and adjustment disorder.…”
Section: Resultsmentioning
confidence: 99%